Knowledge and readiness for inter professional education and collaborative practice among undergraduate nursing students in a Middle Eastern country - A pilot study. (May 2021) - Arulappan, Judie; Matua, Gerald Amandu; Alzaabi, Omar; Vincent, Sophia Cyril; Jayapal, Sathish Kumar; Al Sabei, Sulaiman Dawood; Seshan, Vidya
Abstract: Background: Inter Professional Education and Collaboration (IPEC) is grounded on mutual respect, enhances collaborative practice, and increases satisfaction among health care professionals. Purpose: The study was conducted to assess the level of knowledge and readiness for IPEC among nursing students. Methods: The student's level of knowledge was assessed using a 20 item questionnaire while their readiness for IPEC was measured using the Readiness for Interprofessional Learning Scale (RIPLS) comprising 19 items. A total of 125 nursing students participated in the study and data was analyzed using Statistical Package for the Social Sciences (SPSS) version 25 Discussion: The mean level of knowledge was 44.41 with SD of 4.72. The mean readiness score was 79.09 with the SD of 11.77. There is no significant association between the knowledge and readiness of nursing students regarding IPEC and their demographic variables at 0.05 confidence level. Conclusions: Majority of the students had moderately adequate knowledge about IPEC and high level of readiness towards IPEC. This implies that when appropriately implemented, the students will reap the benefits of IPEC, which has the potential to improve their ability to provide holistic nursing care to their patients.